CVD 103-HgR live, attenuated cholera vaccine strain viability in drinking waters from the US and Europe - Duffin, R. Paul (Sci Rep, 2021)
CVD 103-HgR live, attenuated oral cholera vaccine strain is indicated for single dose immunization against Vibrio cholerae, the causative agent for cholera. The vaccine packets containing buffer powder and lyophilized CVD 103-HgR are reconstituted in water and consumed. Studies were performed to explore the viability of CVD 103-HgR in drinking waters from common sources. CVD 103-HgR vaccine was reconstituted in bottled and tap waters from the United States and Europe, and viability was measured via colony forming units assay. Chemical analysis of select water samples was used to identify chemicals that have a negative effect on CVD 103-HgR viability. CVD 103-HgR titers were stable in all bottled waters tested, including purified bottled water, bottled spring water, and sparkling waters. However, tap water from certain cities in the US and Europe affected viability and are not compatible with vaccine. Water chemistry revealed that these tap waters contained copper, likely leached from copper plumbing. These studies give high confidence in the stability of CVD 103-HgR reconstituted in a variety of bottled waters. Waters containing copper, including tap water, should not be used to reconstitute CVD 103-HgR strain oral vaccine due to the common use of copper plumbing.